UV Activation of Persulfate for Removal of Penicillin G Antibiotics in Aqueous Solution - Samira Norzaee; Edris Bazrafshan; Babak Djahed; Ferdos Kord Mostafapour; Razieh Khaksefidi (The Scientific World Journal)
Penicillin G (PG) is one of the most widely consumed antibiotics around the world. Release of PG in environment may lead to contamination of water resources. The aim of the present work is to assess feasibility of applying UV-activated persulfate process in removal of PG from aquatic environments. The study examined the effect of pH (3–11), persulfate initial concentration (0.5–3 mM), reaction time (15–90 minutes), and initial concentration of PG (0.02–0.14 mM) on PG decomposition. Also, the pseudo-first-order kinetic model was used for kinetic analysis of PG removal. The results indicated that UV-activated persulfate process can effectively eliminate PG from water. The highest PG removal efficiency was obtained as 94.28% at pH 5, and the decomposition percentage was raised by increasing persulfate dose from 0.5 to 3 mM and the reaction time from 15 to 90 minutes. Besides, the removal efficiency decreased through increasing the initial concentration of PG. UV-activated persulfate process effectively decomposes PG and eliminates it from water.